(3Sde GdYhGdi ef GdaQb dfjd GdeYGdi hGdTQas ((3YHO Gddg Hf YHO GdhGMO Hf YHO GddWja Hf TYjH GdYHO GdSdGe s)
(3ChdgG (B:s
(3GdeLO HGdLO GdELJgGO aGNdY cShg GdcSd hGaUe YOi GdYLR hGZfe aQUI GdCLd s
(3BNQgG (B:s
(3hdG CYhd ai GdOfjG Ydi CMO EdG Ydi Gddg QHi OGFekG Yhdi hGdBd hGdUMH hGdCRhGL cdge eG SGQ SGQ dbUO ChVM GdSHd JeJ GdefXheI GdZRGA s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3GdfSNI HgG MhGTs
(3HgG Jedc HGSe YHO Gddg Hf YHO GdhGMO Hf YHO GddWja Hf TYjH YHO GdSdGe hJGQjNI (B1294s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdeLGejYs